0456 Natural History of Insomnia: Sleep Reactivity Predicts New-Onset Acute Insomnia. (27th May 2020) - Vargas, I; Drake, C; Muench, A; Boyle, J; Morales, K; Grandner, M; Ellis, J; Perlis, M
Abstract: Introduction: Greater vulnerability to stress-related sleep disturbance (i.e., sleep reactivity) is a risk factor for chronic insomnia (CI). What has not been investigated is whether greater sleep reactivity, as assessed by the Ford Insomnia Response to Stress Test (FIRST), predicts the onset of acute insomnia (AI), and more, whether greater sleep reactivity predicts the transition from AI to CI. Methods: A national cohort of 1, 222 good sleeper subjects (68% female; mean age=53.2 years) were prospectively assessed to estimate the incidence of AI and CI. The FIRST was completed at baseline and sleep diaries were completed on a daily basis for a period of one year. Subjects were categorized based on their FIRST scores (high, FIRST>16; low, FIRST≤16). Subjects were also grouped based on whether they developed AI (two consecutive weeks with a frequency of ≥ 3 nights per week of sleep initiation or maintenance problems) or maintained good sleep (GS; n=896). For those subjects that transitioned to AI (n=326), they were also grouped based on whether or not they developed CI (insomnia ≥ 3 nights/week for at least three months; n=23). Chi-square analyses were performed to determine if higher FIRST scores at baseline predicted the incidence of AI or CI. Results: 32.5% of subjects in the high FIRST group met criteria for AI at some point during the one-year interval, whereas 22.5% of subjects in the low FIRST group experienced AI (χ  2 =15.2, p<.001). In contrast, FIRST did not predict CI status (low FIRST, 8.5% CI, high FIRST, 5.6% CI; χ  2 =1.1, p=.30). Conclusion: Greater sleep reactivity predicted incident AI but not the onset of CI. While these findings suggest that sleep reactivity may be a predisposing factor for AI, data are not consistent with previous findings showing FIRST scores are predictive of the development of CI. It's possible that the present study was underpowered to detect these differences, given that the incidence of CI was low (less than 2% of the total sample). Additional analyses are ongoing to evaluate the temporal association between stressful life events and AI in subjects with high and low FIRST scores. Support: Perlis: NIH R01AG041783, K24AG055602